From target to actor: Contagion of honesty and deception across buyer–supplier negotiations. Issue 2 (4th September 2022) - Ried, Leopold; Eckerd, Stephanie; Kaufmann, Lutz; Carter, Craig R.
Abstract: Understanding negotiators' decision‐making processes in buyer–supplier relationships has been of key interest to behavioral operations and supply chain management researchers. We hypothesize that through the exposure to various counterparts in the supply chain network, negotiators' behaviors are influenced by others' behaviors and prone to behavioral contagion —where the target adopts the behavior he/she is subjected to and exhibits it toward a nonpartisan counterpart. This paper examines such contagion where targets turn into actors of honesty and deception across buyer–supplier negotiations. We analyzed text responses from two studies employing scenario‐based negotiation experiments with 350 and 424 individuals with B2B sales experience and tested for the effects of previously received behavior (honesty/deception) and different frequency levels of the received behavior. Our results show contagion effects for honesty and deception in both studies. These effects are largely independent from the frequency with which the behaviors have been received, suggesting that a low stimulus frequency suffices to induce contagion of honest and deceptive behaviors across buyer–supplier negotiations. Interestingly, in contrast to our hypothesized key mechanism based on the extant literature, neither injunctive nor descriptive social norms mediated the relationship between received and acted behaviors. We offer alternative explanations and discuss implications for theory and practice. Highlights: Both honesty and deception are contagious across buyer‐supplier negotiations; negotiators are more likely to show the behaviors they were subjected to in previous negotiations in a new negotiation with a different counterparty. It is largely irrelevant how often the negotiator experiences honest or deceptive behavior in order to induce this contagion; in our experiment, once was sufficient. We advise companies to establish or maintain negotiation practices to potentially avoid the oblivious spreading of behaviors, for instance by actively recapitulating previous negotiations and conducting negotiations in teams of two or more.